2020
DOI: 10.1002/cncr.33050
|View full text |Cite
|
Sign up to set email alerts
|

Emerging cancer incidence trends in Canada: The growing burden of young adult cancers

Abstract: BACKGROUND: Recent studies have identified increases in cancer incidence among younger adults for some cancers. This study examined incidence trends for 28 cancers in Canada by age and birth cohort from 1983 to 2012. METHODS: Canadian incidence data for 20 to 84 year-olds were obtained from the Cancer Incidence in Five Continents Plus database. Age-period-cohort modeling was used to estimate the average annual percentage changes (AAPCs) and incidence rate ratios (IRRs) for 10-year birth cohorts (reference coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 28 publications
0
65
1
3
Order By: Relevance
“…Recent notable findings are the increase in the incidence of stomach cancer (cardia and noncardia gastric cancers combined) among young adults (aged <50 years) in both low‐risk and high‐risk countries, including the United States, Canada, the United Kingdom, Chile, and Belarus 139,140 . A previous US study focusing on noncardia gastric cancer reported that increases among young individuals was largely confined to non‐Hispanic Whites and people living in more affluent counties 141,142 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent notable findings are the increase in the incidence of stomach cancer (cardia and noncardia gastric cancers combined) among young adults (aged <50 years) in both low‐risk and high‐risk countries, including the United States, Canada, the United Kingdom, Chile, and Belarus 139,140 . A previous US study focusing on noncardia gastric cancer reported that increases among young individuals was largely confined to non‐Hispanic Whites and people living in more affluent counties 141,142 .…”
Section: Resultsmentioning
confidence: 99%
“…138 Recent notable findings are the increase in the incidence of stomach cancer (cardia and noncardia gastric cancers combined) among young adults (aged <50 years) in both low-risk and high-risk countries, including the United States, Canada, the United Kingdom, Chile, and Belarus. 139,140 A previous US study focusing on noncardia gastric cancer reported that increases among young individuals was largely confined to non-Hispanic Whites and people living in more affluent counties. 141,142 It has been postulated that the rising prevalence of autoimmune gastritis and dysbiosis of the gastric microbiome, possibly relevant to increased use of antibiotics and acid suppressants, may have contributed to the paradoxical increase of stomach cancer among younger generations.…”
Section: Stomach Cancermentioning
confidence: 99%
“…Otro de los cánceres que está incrementándose de forma rápida entre la población AJA es el cáncer de tiroides. Hay autores que explican esta alarmante subida por el sobre diagnóstico y sobre tratamiento de lesiones que si se las dejase sin actuar no causarían problemas (Heer, et al, 2020;Topstad & Dickinson, 2017). También es estadísticamente significativo el aumento entre los jóvenes del cáncer de testículo en todos los países analizados, excepto en el continente africano (Gupta et al, 2020).…”
Section: Incidencia Del Cáncer En Los Adolescentes Y Jóvenes Adultos (Aja)unclassified
“…Moreover, owing to some paradoxical observations, it is now speculated that in addition to H. pylori infection, diet and host genetic factors are responsible for the progress from H. pylori -induced inflammation to GC [ 9 , 11 , 12 ]. A few recent studies also proposed that the increasing prevalence of autoimmune gastritis and dysbiosis of gut microbiota and increased use of antibiotics and acid suppressants, might have led to the variation in the risk of GC, primary gastric lymphoma (PGL), and neuroendocrine carcinoma [ 13 , 14 , 15 ]. Inter-individual variations on disease susceptibility of GC can also be influenced by other infections such as Epstein-Barr virus, intestinal helminths, and host genetic differences in cytokine genes [ 9 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%